Associations between Social Competence, Perceived Parents’ Prosocial Educational Goals and Adolescents’ Hate Speech Perpetration in School - Kansok-Dusche, Julia (Victims & offenders, 2024)
Hate speech is a global challenge, requiring research on adolescents’ hate speech perpetration in schools. We examined whether perceived parents’ prosocial educational goals moderate the association between social competencies (social perspective-taking, openness to diversity) and hate speech perpetration in schools. In total, 1,719 adolescents (aged 11–18 years) from 22 Swiss schools completed selfreport questionnaires (December 2020 to April 2021). Social perspective-taking and hate speech perpetration correlated negatively, alongside openness to diversity and hate speech perpetration. Perceived parents’ prosocial educational goals strengthened the negative association between openness to diversity and hate speech perpetration in schools but did not moderate the association with social perspective-taking.